Options to Narrow New Zealand's Saving – Investment Imbalance - Anne-Marie Brook (New Zealand Government, The Treasury, 2014)
The Treasury has, at times, suggested giving greater consideration to reforms to narrow the Saving-Investment gap. However, there has been less discussion of specific policy options for doing this. This paper helps to fill the gap by asking what policy reforms could help to narrow the Saving-Investment gap in New Zealand. Lower per capita growth in the capital stock overall does not seem a desirable goal, given the relatively capital shallow nature of the New Zealand economy. This suggests a need for a significantly higher rate of national saving. Previous recommendations to boost national saving have often focused on higher government saving. This paper agrees that higher public saving is desirable but argues that efforts to boost private sector saving rates are at least as important. Potential policy options to boost private sector saving include tax policy changes, a range of different retirement income policy settings and policies that affect the housing market. Internationally, New Zealand stands out as being one of the only OECD countries where individuals do not have access to any significantly tax-preferred saving vehicles other than property. Tax reform thus has potential to both raise the level of saving and improve its composition. One option may be to reduce the tax rate on capital income, such as by extending the existing PIE regime, although such a reform would need to be packaged together with other tax changes to mitigate the equity and revenue impacts. Another option would be to move toward a private save-as-you-go (SAYGO) pension system, which would pair compulsory savings with means-testing of New Zealand Superannuation (NZS). At the same time, there is a growing body of evidence pointing to the effectiveness of default policies that nudge individuals to save more (as KiwiSaver does). Finally, a number of policies are considered that would dampen house price inflation, which may help to boost private saving.
Keywords: D9; E21; H55; O16; 330; Saving; Investment; Tax; Pension policy; Sparen; Kapitalertragsteuer; Steuerwirkung; Haushaltseinkommen; Neuseeland